2015
DOI: 10.1007/s10943-015-0045-2
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Positive Psychology Go Hand in Hand: An Investigation of Multiple Empirically Derived Profiles and Related Protective Benefits

Abstract: We investigate the relationship between personal spirituality and positive psychology traits as potentially presented in multiple profiles, rather than monolithically across a full sample. A sample of 3966 adolescents and emerging adults (aged 18-25, mean = 20.19, SD = 2.08) and 2014 older adults (aged 26-82, mean = 38.41, SD = 11.26) completed a survey assessing daily spiritual experiences (relationship with a Higher Power and sense of a sacred world), forgiveness, gratitude, optimism, grit, and meaning. To a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 54 publications
4
37
0
Order By: Relevance
“…In a study of 3966 adolescents, emerging adults and older adults, also using the Brief MMRS, low spirituality was associated with low depression for adolescents (Barton and Miller 2015). Similarly, in a nationwide survey of young Canadians with regular church involvement, poorer levels of emotional well-being and physical health were found compared to those who did not participate in religious services (Michaelson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 3966 adolescents, emerging adults and older adults, also using the Brief MMRS, low spirituality was associated with low depression for adolescents (Barton and Miller 2015). Similarly, in a nationwide survey of young Canadians with regular church involvement, poorer levels of emotional well-being and physical health were found compared to those who did not participate in religious services (Michaelson et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Descriptive statistics were used to determine the levels of spirituality, psychological well-being and suicide probability of the participants. Result showed that the level of spirituality of the participants is moderate (M=104.94; SD=19.28) an indication that lesbian and gay Filipino youth are often going through a process of spiritual individuation, which will eventually result to a more clearly defined and differentiated concept of spirituality as time progresses (Barton & Miller, 2015). The participants also appear to be moderate in terms of their psychological well-being (M=166.70; SD=23.69).…”
Section: Resultsmentioning
confidence: 95%
“…There is a possibility that the emphasis of spirituality on meaning in life was obscured by the other dimensions of psychological well-being, such as search for meaning and purpose, as well as positive relations (van Dierendonck, 2004). In addition, it can be assumed that the limited ability of lesbian and gay individuals to access their inner resources and have a satisfying relationships with God or a higher power was not enough to contribute to the reduction of suicide behavior due to the process of spiritual individuation (van Dierendonck, 2004;Barton & Miller, 2015). Moreover, spirituality had always been positively associated with psychological well-being (Kamitsis & Francis, 2013;Sacco, Park, Suresh, & Bliss, 2014;Jafari et al, 2010;von Humboldt, Leal, & Pimenta, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is a possibility that the emphasis of spirituality on meaning in life was obscured by the other dimensions of psychological well-being, such as search for meaning and purpose, as well as positive relations (van Dierendonck, 2004). In addition, it can be assumed that the limited ability of lesbian and gay individuals to access their inner resources and have a satisfying relationships with God or a higher power was not enough to contribute to the reduction of suicide behavior due to the process of spiritual individuation (van Dierendonck, 2004;Barton & Miller, 2015). Moreover, spirituality had always been positively associated with psychological well-being (Kamitsis & Francis, 2013;Sacco, Park, Suresh, & Bliss, 2014;Jafari et al, 2010;von Humboldt, Leal, & Pimenta, 2015).…”
Section: Discussionmentioning
confidence: 99%